Speech aggression as a manifestation of dominance: pragmalinguistic aspects - Novikova Lidia; Shuraeva Fotina (E3S Web of Conferences, 2021)
The authors investigate the phenomenon of speech aggression in texts of various directions. The destruction of the cultural system, built exclusively on religious unity, marks the end of the Middle Ages, coming towards the end of the fourteenth century. It was then that the formation of a new principle begins, which is that “objective reality and its meaning are sensual. Reality is comprehended not with the help of revelation, transposed by selected religious practices, but through the senses. The role of anthropocentrism is growing both at the philosophical and cultural, and at the speech-thinking (linguo-cognitive) levels. А cultural system based on such a premise idealistic. In it, feeling is balanced by intellect, faith by science, empirical perception by intuition. Its values belong to both the Earth and Heaven. Her world is both sensual and supersensible.